Pemertahanan Bahasa Indonesia Melalui Media Sosial Youtube pada Generasi Z - Iqram Anwar Ramadhani; Jumadi Jumadi; Dwi Wahyu Candra Dewi (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
Human communication can be carried out through the use of language. Indonesian is not merely a tool for communication but also a unifying force for the Indonesian people. A language that adheres to its rules without deviation in many aspects is the official language of Indonesia and is used as a form of verbal or written communication, both formal and informal. The Indonesian people should be proud to have a language that can represent their feelings and thoughts. The existence of the Indonesian language in its current condition demands that the identity of the Indonesian language be cultivated and socialized by every Indonesian citizen. Mastering and loving the national language as an Indonesian citizen who loves the homeland is a matter of pride, identity, and a hallmark of Indonesia, as it is the language of unity. Even though you have learned foreign languages, it does not mean that you immediately forget the Indonesian language and its prestige. With our language of unity, which is Indonesian, loving and using Indonesian in accordance with language rules and maintaining it is an implication for preserving the existence of Indonesian through linguistic attitudes.